Correlation of Sperm Nuclear Chromatin Condensation Staining Method with Semen Parameters and Sperm Functional Tests in Patients with Spinal Cord Injury, Varicocele, and Idiopathic Infertility - Salsabili, Nasser; Mehrsai, Abdorasoul; Jalalizadeh, Babak; Pourmand, Gholamreza; Jalaie, Shohreh (Urology Journal, 2009)
Introduction: Our aim was to investigate sperm nuclear chromatin condensation and its correlation with semen parameters and vitality test in infertile patients with spinal cord injury (SCI), varicocele, and idiopathic infertility. Materials and Methods: Sperm chromatin condensation was determined by aniline blue staining in 22 SCI-injured infertile men, 20 with varicocele, and 28 with idiopathic infertility. The results were compared with the semen analysis parameters and the hypo-osmotic swelling test results. Three grades of staining for sperm heads were distinguished: unstained, showing sperm maturity (G0); partially stained (G1); and completely stained, showing sperm immaturity (G2). The total score was calculated as: (G0 × 0) + (G1 × 1) + (G2 × 2). Results: In all groups, the total staining score was higher than 75%, corresponding to a high degree of immaturity of sperm. Patients with SCI had a less sperm nuclear chromatin condensation and chromatin stability than patients with idiopathic infertility and varicocele (total scores, 98% versus 89% and 88%, respectively; P < .01). All of the patients had normal hypo-osmotic swelling test results. Sperm counts for all patients were within the reference range. The mean percentages for normal motility and morphology of the sperm were 15.5% and 15% for patients with SCI, 43% and 15% for patients with varicocele, and 62.5% and 54% for patients with idiopathic infertility. There was no correlation between sperm nuclear chromatin condensation and semen analysis parameters. Conclusion: Aniline blue staining for sperm nuclear chromatin condensation is a method independent of semen analysis and demonstrates the internal structural defects of sperm. This method may have a predictive value in assessing fertility.